Surface‒Aerosol Stability and Pathogenicity of Diverse Middle East Respiratory Syndrome Coronavirus Strains, 2012‒2018 - Neeltje van Doremalen (Centers for Disease Control and Prevention, 2021)
Middle East respiratory syndrome coronavirus (MERS-CoV) infects humans and dromedary camels and is responsible for an ongoing outbreak of severe respiratory illness in humans in the Middle East. Although some mutations found in camel-derived MERS-CoV strains have been characterized, most natural variation found across MERS-CoV isolates remains unstudied. We report on the environmental stability, replication kinetics, and pathogenicity of several diverse isolates of MERS-CoV, as well as isolates of severe acute respiratory syndrome coronavirus 2, to serve as a basis of comparison with other stability studies. Although most MERS-CoV isolates had similar stability and pathogenicity in our experiments, the camel-derived isolate C/KSA/13 had reduced surface stability, and another camel isolate, C/BF/15, had reduced pathogenicity in a small animal model. These results suggest that although betacoronaviruses might have similar environmental stability profiles, individual variation can influence this phenotype, underscoring the need for continual global viral surveillance.